Between professional values, social regulations and patient preferences: medical doctors' perceptions of ethical dilemmas. Issue 4 (18th November 2017) - Bringedal, Berit; Isaksson Rø, Karin; Magelssen, Morten; Førde, Reidun; Aasland, Olaf Gjerløv
Abstract : Background: We present and discuss the results of a Norwegian survey of medical doctors' views on potential ethical dilemmas in professional practice. Methods: The study was conducted in 2015 as a postal questionnaire to a representative sample of 1612 doctors, among which 1261 responded (78%). We provided a list of 41 potential ethical dilemmas and asked whether each was considered a dilemma, and whether the doctor would perform the task, if in a position to do so. Conceptually, dilemmas arise because of tensions between two or more of four doctor roles: the patient's advocate, a steward of societal interests, a member of a profession and a private individual. Results: 27 of the potential dilemmas were considered dilemmas by at least 50% of the respondents. For more than half of the dilemmas, the anticipated course of action varied substantially within the professional group, with at least 20% choosing a different course than their colleagues, indicating low consensus in the profession. Conclusions: Doctors experience a large range of ethical dilemmas, of which many have been given little attention by academic medical ethics. The less-discussed dilemmas are characterised by a low degree of consensus in the profession about how to handle them. There is a need for medical ethicists, medical education, postgraduate courses and clinical ethics support to address common dilemmas in clinical practice. Viewing dilemmas as role conflicts can be a fruitful approach to these discussions.